COMPLEX SURGICAL TREATMENT OF PATIENTS WITH HIGH-GRADE BRAIN TUMORS - Sh.N. Tashmatov,; R.T. Kadyrbekov,; G.A. Alikhodjaeva,; T.M. Akhmediev,; Z.Sh. Shamuratov, (Central Asian Journal of Medicine, 2023)
Currently, there are numerous complex methods of treatment of glial brain tumors, namely: chemotherapy, radiation therapy, stereotactic radiosurgery, surgical removal of the tumor. The surgical method of treatment can be considered one of the most effective, since removal of the focus eliminates the neoplasm as a source of volumetric impact and the cause of cerebral edema. The operation, significantly and rather quickly improves the general condition of the patient, leads to regression of cerebral and neurological symptoms, especially with large tumors. The objective. To improve the results of surgical treatment of patients with malignant brain tumors (grade III-IV WHO) using complex treatment methods. Materials and methods. During the period from 2009 to 2019 there are 2343 patients with glial brain tumors were examined and operated in the Republican specialized scientific practical medical center of neurosurgery. Patients underwent a comprehensive examination, including clinical and neurological examination of related specialists (fundus examination, neuro-ophthalmological examination, vestibulograms), instrumental research methods (CT, MRI of the brain, tractography of the pathways, if indicated, contrast examination and angiography of intracranial arteries), microsurgical removal of the tumor, histological verification of the biopsy and subsequent irradiation with a neutron capture therapy on the basis of the Institute of Nuclear Physics of the Academy of Sciences of the Republic of Uzbekistan. Results. Compensated state 70 points and above - 1213 (51.7%) patients, subcompensated state 60-50 points - 1031 (44.0%) patients, decompensated state 40 points and below - 78 (3.3%) patients were noted. Analyzing operated patients with glial brain tumors, 1033 (44.1%) patients were discharged in good recovery, 729 (31.1%) patients were moderately disabled, 534 (22.8%) patients were severely disabled, mortality - 28 (1.7%) patients. Radiation therapy was received by 1169 (50.4%) patients. Relapses in glial brain tumors were found in 166 (7.2%) patients. Conclusion. The maximal radical removal of the tumor and the use of radiation therapy in the treatment of malignant brain tumors allows to achieve good survival of patients and a long relapse-free period.